2019
DOI: 10.3390/atmos10040164
|View full text |Cite
|
Sign up to set email alerts
|

Recent Strengthened Impact of the Winter Arctic Oscillation on the Southeast Asian Surface Air Temperature Variation

Abstract: A previous study indicated that the Arctic Oscillation (AO) and Siberian High (SH) are two important drivers for the interannual variation of winter surface air temperature (SAT) over southeast Asia. This study reveals that the impact of the winter SH on the southeast Asian SAT was stable. By contrast, the connection between the winter AO and southeast Asian SAT displays a pronounced interdecadal change around the late-1990s. Significant impact of the winter AO on the southeast Asian SAT can only be detected a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Although many studies have reported that the AO can influence regional temperature, these influences may not be stable [25][26][27][28][29][30]. For example, Li et al [26] found that the link between the winter AO and an East Asian winter monsoon index experienced a significant interdecadal change during past decades.…”
Section: Introductionmentioning
confidence: 99%
“…Although many studies have reported that the AO can influence regional temperature, these influences may not be stable [25][26][27][28][29][30]. For example, Li et al [26] found that the link between the winter AO and an East Asian winter monsoon index experienced a significant interdecadal change during past decades.…”
Section: Introductionmentioning
confidence: 99%
“…Positive R values indicate a positive correlation between x and y; negative R values indicate a negative correlation between x and y. Significance levels of the correlation coefficient were estimated according to the two-tailed Student t-test [40].…”
Section: Correlation Analysismentioning
confidence: 99%
“…This pattern leads to anomalous westerly wind belts in the mid‐latitudes, transporting warm ocean air to the continents and resulting in milder winter SAT in the mid‐latitudes (Thompson & Wallace, 2000). Interestingly, some studies suggested that the effect of the AO on regional SAT might be unstable (Blackport & Screen, 2020; Chen & Song, 2019; Gong et al., 2018). The NAO, another important mode of atmospheric variability at mid‐high‐latitudes in the Northern Hemisphere, also plays a crucial role in Northern Hemisphere winter SAT.…”
Section: Introductionmentioning
confidence: 99%